TROSO FABRIC MOTIFS OF TARO LEAVES AND PEACOCKS AS OBJECTS OF BATIK WORK - Ridho, Mohammad Jamil Ainur (Eduarts: Jurnal Pendidikan Seni, 2025)
This research focuses on the decline of hand-written batik practices in Troso Village, Jepara, which is better known as the center of ikat weaving. The lack of successors of batik artisans and mastery of weaving has made local handmade batik almost disappear. Troso Village actually has tremendous potential in traditional motifs such as the taro leaf (lompong) and the meaningful image of the peacock. This study aims to explore the visual and philosophical strengths of Troso's weaving patterns and peacocks, and to produce mixed-media batik works based on local motifs as a cultural revitalization effort. The approach applied is descriptive qualitative, with data collection techniques through field observation, interviews, and document analysis. The motifs of taro leaves and peacocks were chosen because they have strong visual appeal and symbolic values that symbolize survival and cultural beauty. Both are combined in batik tulis with a visual arrangement that emphasizes the balance between geometric and figurative patterns. The research findings indicate that the use of local motifs combined with attractive media in written batik can revive people's interest in batik art and strengthen the visual identity of the village. This work plays a role not only in cultural preservation, but also creates opportunities for local creative economic development through batik products that have aesthetic and contextual value.